Trump’s Tweets vs. Actual Policy - Huan, Amanda (2018)
When Donald J. Trump took over as president, there were concerns that the US would become more isolationist given his ‘America First’ approach. Trump’s campaign rhetoric had clearly promised such a shift. One year into his presidency, has the US moved away from multilateralism?